Obtention, characterization, and herbicide diquat carrier/release properties by nanocomposite hydrogels based on the polysaccharides and zeolite for future use in agriculture - Tanaka, Fabrício C. [UNESP]; Yonezawa, Uilian G. [UNESP]; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (Elsevier, 2023)
This work aims to develop new hydrogel nanocomposites based on polysaccharides (methylcellulose (MC) or chitosan (CH)) with zeolite, supported by a poly(methacrylic acid)–co-polyacrylamide (PMAA-co-PAAm) network for agriculture applications, such as water decontamination, and released control systems. The incorporation of zeolite on the nanocomposites has been confirmed by the characteristic peaks of zeolite in nanocomposites through Fourier transform infrared spectroscopy (FTIR) spectra and X-ray diffraction (XRD) patterns. Scanning electron microscopy (SEM) analyzes showed a decrease in the pore volume on the nanocomposites and the presence of micropore at the wall porous structure. The chain elasticity and water retention of the hydrogel were affected by changes in pH rate, for example, the MC nanocomposite swelling values growth from 2.6 g/g at pH 1 to 4.4 g/g at pH 5. The sorption and desorption of diquat studies showed that an increase in the interaction sites provided by the zeolite negative surface charges caused an increment in the attraction forces, which afford the interchange between the diquat molecules and the desorption medium ions. These results indicated that intrinsic and extrinsic factors can affect desorption, and a better understanding of these phenomena can be supplemental in a significant way in the more efficient application of these materials in agricultural systems.
Keywords: Controlled released; Hydrogel; Nanocomposite, diquat; Polysaccharide